Prediction of Bread Raw Material Stock At Al-Fattah Bakery and Cake Aek Teluk Kiri using SMA method - Handayani, Dewi; Handayani, Masitah; Syahputra, Abdul Karim (Sistemasi: Jurnal Sistem Informasi, 2024)
AL- Fattah Bakery and Cake is a company engaged in the production and sale of pastries. In managing raw material inventory, you must ensure sufficient inventory for sales, minimizing the time and costs required. Inventory control is an effort carried out by a company to optimize sales and seek as little risk as possible. The problem faced by AL- Fattah Bakery and Cake for each branch in Asahan Regency is the difficulty in determining the amount of raw material inventory that must be produced in the following month in order to continue to meet customer demand and not cause accumulation over a long period of time and maintain the stability of raw material stock. . Because if there is a buildup of stock, it could result in the product expiring and failing to be distributed to customers. This is caused by customer demand which changes every month following existing trends. The aim of this research is to predict raw material supplies using the SMA (Single Moving Average) method at AL- Fattah Bakery and Cake for each branch in Asahan Regency. Based on the results of the research that has been carried out, the Single Moving Average (SMA) method can help AL- Fattah Bakery and Cake Aek Teluk Kiri with the Single Moving Average Method in predicting the supply of bread raw materials for the following month.